Alden family papers
Correspondence, sermons, legal notes, receipts, land grants, leases, household accounts, business accounts, school memorandum and lesson books, militia muster and provision accounts, and daybooks of the Joseph Alden family of Bridgewater, Mass., and Stafford, Conn. Includes notes (circa 1793) for a history of Randolph, Mass. Names represented include Daniel Alden, Samuel Alden, and Seth Alden and the Cary (Carey), Edson, Haywood, Hooper, Shaw, and Sprague families.
Collection material in English.
Keywords: Alden, Daniel, -- 1691-1767.; Alden, Joseph, -- 1624-1697.; Alden, Samuel, -- 1705-1785.; Alden, Seth, -- 1709-1784.; Alden family; Carey family; Edson family; Haywood family; Hooper family; Shaw family; Sprague family; Bridgewater (Mass.) -- History; Connecticut -- Social life and customs; Massachusetts -- Social life and customs; Randolph (Mass.) -- History; Stafford (Conn.) -- History